1995
DOI: 10.1029/94tc01676
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of the Gangdese batholith, southern Tibet: A history of episodic unroofing

Abstract: The Gangdese batholith, southern Tibet, was part of an Andean-type arc at the southern margin of Asia prior to the collision of India and Asia at approximately 50 to 40 Ma. Fission-track and 4øAr/39Ar analyses of 28 rocks from 10Gangdese granitoid plutons along an -250 km length of the batholith in the Lhasa region provide a detailed understanding of the age and the postcrystallization erosional and tectonic history of these rocks. These data suggest a range of ages for these plutons of 94 to 42 Ma, with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(117 citation statements)
references
References 37 publications
11
105
1
Order By: Relevance
“…This event is observed not only at Zedong, but also 60 and 120 km further west along strike, respectively, at Samye and Quxu (Plate l) [Copeland et al, 1994]. This concordance of ages within regime 1 is perhaps the best evidence that thrusting was underway at 27 Ma.…”
Section: Discussion Crustal Thickening In Southern Tibetmentioning
confidence: 63%
See 2 more Smart Citations
“…This event is observed not only at Zedong, but also 60 and 120 km further west along strike, respectively, at Samye and Quxu (Plate l) [Copeland et al, 1994]. This concordance of ages within regime 1 is perhaps the best evidence that thrusting was underway at 27 Ma.…”
Section: Discussion Crustal Thickening In Southern Tibetmentioning
confidence: 63%
“…This map relation indicates differential unroofing along strike: the structural level of pluton exposure near Lhasa is between 10 to 15 km as indicated by thermochronometry and barometry [Copeland et al, 1987[Copeland et al, , 1994 , whereas the widespread preservation of volcanic rocks in this belt suggests much less denudation west of Renbu. Spatially corresponding to the preservation of volcanic cover in the Gangdese Shan is the appearance, to the south, of the Xigaze Group (Plate 1).…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The plutonic rocks of the Gangdese batholith, comprising granite, granodiorite, and tonalite, have a range of crystallization ages from ∼120 to 40 Ma [Harris et al, 1988]. The batholith also shows two distinct periods of plutonism that are broadly 120-90 and 70-40 Ma [Copeland et al, 1995]. Chung et al [1998] found evidence for tectonic and magmatic activity in the Tibetan plateau (as recorded by potassic volcanic rocks) from 30 to 40 Ma.…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…Many of these tectonic units may potentially have contributed to the Bengal basin detritus used in this study. Copeland et al [1995] studied the rocks of the Gangdese batholith in the southern Tibetan plateau (Figure 1) and found crystallization ages in the range of 94 to 42 Ma. The plutonic rocks of the Gangdese batholith, comprising granite, granodiorite, and tonalite, have a range of crystallization ages from ∼120 to 40 Ma [Harris et al, 1988].…”
Section: Results and Interpretationsmentioning
confidence: 99%